Analytical generation of stress-strain properties of coir fiber reinforced composites in axial compression - Jorillo, Pablo A. (Philippine Engineering Journal)
This paper examines the compressive stress-strain properties of concrete and mortar matrix reinforced with a natural cellulosic fiber i.e., coconut (coir) fiber. An extensive experimental program was carried out to investigate the inter-relationship of fiber reinforcing parameters such as fiber volume fraction, length or aspect ratio in combination with different grades of concrete or mortar matrices and the resulting stress and strain properties of the fiber cement composite materials in axial compression. In order to characterize the stress strain curve of a fiber concrete/mortar, a fractional second degree polynomial model developed by Sargin (1971) and modified by Wang et al. (1978) was used in this study. Findings showed that the analytical model can satisfactorily generate the complete stress strain properties of a fiber composite material based solely on the knowledge of material properties of the composite constituents.